Dynamics of Novel Photoactive AgCl Microstars and Their Environmental Applications. Issue 1 (19th December 2016) - Simmchen, Juliane; Baeza, Alejandro; Miguel‐Lopez, Albert; Stanton, Morgan M.; Vallet‐Regi, Maria; Ruiz‐Molina, Daniel; Sánchez, Samuel
Abstract: In the field of micromotors many efforts have been taken to find a substitute for peroxide as fuel. While most approaches turn towards other toxic high energy chemicals such as hydrazine, we introduce here an energy source that is widely used in nature: light. Light is an ideal source of energy and some materials, such as AgCl, have the inherent property to transform light energy for chemical processes, which can be used to achieve propulsion. In the case of silver chloride, one process observed after light exposure is surface modification, which leads to the release of ions, generating chemo‐osmotic gradients. Here we present endeavors to use those processes to propel uniquely shaped micro‐objects of microstar morphology with a high surface‐to‐volume ratio, study their dynamics and present approaches to go towards real environmental applications. Abstract : Control of precipitation dynamics has been used to synthesize AgCl particles with a range of shapes from cubes to octapod‐shaped microstars. The AgCl microstars can act as self‐propelling micromotors in response to light. In addition, they show promise for the photocatalytic degradation of organic molecules and antibacterial applications (center panel).